Isolation of marine bacteria inhibitory to shrimp bacterial pathogens - Jayanth, K; Jeyasekaran, G; Shakila, R Jeya; Shanmugam, S A (Indian Journal of Fisheries, 2011)
Pigmented bacteria from seawater, sediment, seaweeds, bivalves and submergedsubstrates from Tuticorin coast were screened for the antagonistic activity. Ofthe 166 strains isolated, 15 showed inhibitory activity against shrimp bacterialpathogens. Alteromonas was the antagonistic marine bacteria and it exhibiteda wide antibacterial spectrum against various shrimp bacterial pahtogens viz.,Vibrio harvyi, V. fischeri and V. alginolyticus. One strain of Alteromonas (A6)showed greater antagonism against the shrimp bacterial pathogens. Resultssuggest that these antagonistic marine bacteria could be used as biocontrolagents in the shrimp culture systems